Reading of two works by Liliana Ancalao: Resuello and Rokiñ: Provisions for a journey through the “epistemology of the carrier bag” (Anclajes, 2024)
This article analyzes the work of poet and essayist Liliana Ancalao through a reading of her books Resuello (2018) and Rokiñ: Provisions for a trip (2021), as well as through conversations with the author between 2018 and 2022. The article follows a qualitative and interpretative methodology, and follows Donna Haraway's "epistemology of the carrier bag", a perspective that centers the excluded history and the unsaid, and aims at dismantling gender, race, ethnic and class stereotypes. From this line of thought, we focus on the following significant themes: the polysemy of the arrow, the importance of moving through urban spaces to see the indigenous past, and the need to make the mechanisms of colonial domination evident.
Keywords: Liliana Ancalao; Narrative; Original Towns; 19th - 21st Centuries; Mapuches